Integrated Biochar–Compost Amendment for Zea mays L. Phytoremediation in Soils Contaminated with Mining Tailings of Quiulacocha, Peru. - Virú-Vasquez, Paul Hermes (2025)
This study evaluated the phytoremediation of mine tailing-contaminated soils in Quiulacocha, Peru, using the combined application of biochar and compost, with Zea mays L. (maize) serving as the phytoremediator due to its high biomass production and stress tolerance. A factorial experimental design was implemented, varying two main factors: the mining tailings dose (30% and 60% w/w) and the biochar pyrolysis temperature (300 ◦C and 500 ◦C). The mine tailings were characterized by high concentrations of heavy metals and unfavourable physico-chemical properties (pH, low organic matter), whereas the biochar, produced from pine forest residues, and the compost, derived from urban organic waste, exhibited attributes that enhance soil quality. During the pot experiment, response variables including the Bioconcentration Factor (BCF) and Translocation Factor (TF) for various metals were evaluated to assess the capacity for contaminant immobilization and their distribution between plant roots and aerial tissues. The results demonstrated that the incorporation of biochar and compost significantly improved soil quality by increasing pH, cation exchange capacity, and nutrient retention, while simultaneously reducing the bioavailability of heavy metals and limiting their translocation to the aerial parts of maize. Factorial analysis further indicated that both the tailings dose and biochar pyrolysis temperature significantly influenced the efficacy of the phytoremediation process. In conclusion, the combined application of biochar and compost presents an effective and sustainable strategy for rehabilitating mine tailing-contaminated soils by stabilizing heavy metals and promoting the safe growth of Zea mays L.